Leveraging institutional echocardiographic registry to assess clinical profiles and outcomes in tricuspid regurgitation - Yasser M. Sammour; Budhaditya Bose; Chloe Kharsa; Sherif F. Nagueh; Neal S. Kleiman; Waqas Qureshi; Nadeen Faza; Joe Aoun; Sadeer Al-kindi; William A. Zoghbi; Sachin S. Goel; Khurram Nasir; et al. (American Heart Journal Plus)
Tricuspid regurgitation (TR) is a common valvular heart disease that is associated with increased morbidity and mortality. We utilized our large institutional echocardiographic registry, integrated with the electronic medical record-based health system registry to identify patients with varying degrees of TR, and to assess its association with long-term outcomes. Patients were categorized by TR severity as none, mild, moderate, or severe. A total of 88,511 unique individuals were included (44.7 % no reported TR, 49.0 % mild, 4.8 % moderate, and 1.5 % severe). Greater TR severity was associated with advanced age, female sex, and Black race, alongside higher prevalence of baseline comorbidities. Patients with moderate or severe TR exhibited worse congestion biomarkers, creatinine, liver enzymes, and reduced platelet counts. Echocardiographically, moderate or severe TR correlated with lower tricuspid annular plane systolic excursion, left ventricular ejection fraction, as well as larger biatrial and left ventricular volumes. There was a significant association between increasing TR severity and all-cause mortality at 3 years from the index echocardiogram compared with no TR (Moderate TR: AdjHR 1.76; 95 % CI 1.63–1.89; Severe TR: AdjHR 2.40; 95 % CI 2.16–2.66), and similarly for hospitalization (Moderate TR: AdjHR 1.14; 95 % CI 1.08–1.20; Severe TR: AdjHR 1.25; 95 % CI 1.15–1.36). In this large cross-sectional analysis, we highlight how institutional echocardiographic registries can be leveraged to identify the burden of TR, including its significant association with higher mortality and healthcare utilization. These findings emphasize the need for heightened clinical attention and potential intervention in patients with significant TR as tricuspid valve therapies evolve.